Menguak Realitas Pertanggungjawaban Pidana dalam Kasus Kecelakaan Lalu Lintas yang Mengakibatkan Korban Meninggal Dunia - Abdaud, Faisal (LP3M, Universitas Muhammadiyah Kendari, 2023)
Traffic accidents resulting in fatalities are categorized as serious traffic accidents. The purpose of this study is to analyze the reality of criminal liability in cases of traffic accidents resulting in fatalities where the victim's family and the perpetrator's family agree to settle. This study uses a normative legal research type. This qualitative study uses a legislative approach, conceptual approach, and case approach. The results of the study show that the traffic accident case involving the perpetrator and victim